2023
DOI: 10.1002/adma.202301668
|View full text |Cite
|
Sign up to set email alerts
|

Tuning 2D Magnetism in Cobalt Monoxide Nanosheets Via In Situ Nickel‐Doping

Abstract: Element doping has become an effective strategy to engineer the magnetic properties of two-dimensional (2D) materials and is widely explored in van der Waals layered transition metal dichalcogenides. However, the high-concentration substitution doping of 2D nonlayered metal oxides, which can preserve the original crystal texture and guarantee the homogeneity of doping distribution, is still a critical challenge due to the isotropic bonding of closed-packed structures. In this work, the synthesis of high-qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] Among them, metal-containing 2D materials have become a research frontier in nano-medicine, benefiting from their strong near-infrared (NIR) light absorption, ultrasonic responsiveness and the capacity to produce reactive oxygen species (ROS). [17][18][19][20] Currently, there are mainly two types of metal-containing 2D materials, depending on whether metal species are decorated on the surface of 2D materials or take up the skeleton structures. Thanks to the performance modulation of metal species, which endows 2D materials with highly catalytic performance as well as light and sonic responsive ability, these materials are well suited for cancer PDT, PTT, CDT, SDT, and other types of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Among them, metal-containing 2D materials have become a research frontier in nano-medicine, benefiting from their strong near-infrared (NIR) light absorption, ultrasonic responsiveness and the capacity to produce reactive oxygen species (ROS). [17][18][19][20] Currently, there are mainly two types of metal-containing 2D materials, depending on whether metal species are decorated on the surface of 2D materials or take up the skeleton structures. Thanks to the performance modulation of metal species, which endows 2D materials with highly catalytic performance as well as light and sonic responsive ability, these materials are well suited for cancer PDT, PTT, CDT, SDT, and other types of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al reported the synthesis of ultrathin cobalt ferrite nanoflakes, which exhibit a Curie temperature as high as 390 K . As these nonlayered 2D magnets possess magnetic order above room temperature and enhanced chemical stability in comparison to most existing van der Waals magnets, they offer remarkable opportunities for constructing practical magnetic heterostructure devices with potential applications. Until now, the investigation of nonlayered magnetic nanoflakes is still in its infancy due to the inadequate means of controllable 2D growth and a limited understanding of the detailed magnetic properties.…”
mentioning
confidence: 99%